Differential accumulation of manganese in three mature tree species (Holoptelia, Cassia, Neem) growing on a mine dump - Raju, D.; Kumar, Sunil; Mehta, Urmil J.; Hazra, Sulekha (Current Science, 2008)
Three trees, including Cassia siamea (Cassia), Azadirachta indica (Neem), Holoptelia integrifolia (Holoptelia) belonging to three different families were identified from a manganese mine tailing dump. Manganese content in dump soil and in the stem, green leaves and dry, fallen leaves of the plants was determined. Values were compared with similar samples collected from normal vegetation. Under control condition, manganese content was highest in Cassia. Distribution of metal in samples collected from the dump site revealed that Holoptelia has a special ability to accumulate high amounts of manganese under stress condition followed by Cassia and Neem. There is no literature on metal accumulation in Holoptelia. Mechanism of manganese sequestration in Holoptelia is different from the other two trees growing in the same soil.
Keywords: Azadirachta indica; Cassia siamea; Holoptelia integrifolia; hyperaccumulator; manganese; mine dump